Nature Inspired Computing Proceedings of CSI 2015 - Panigrahi, Bijaya Ketan; Hoda, M. N.; Sharma, Vinod; Goel, Shivendra; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume comprises the select proceedings of the annual convention of the Computer Society of India. Divided into 10 topical volumes, the proceedings present papers on state-of-the-art research, surveys, and succinct reviews. The volumes cover diverse topics ranging from communications networks to big data analytics, and from system architecture to cyber security. This volume focuses on Nature Inspired Computing. The contents of this book will be useful to researchers and students alike.
EasyOnto: A Collaborative Semi Formal Ontology Development Platform -- Biometric Inspired Homomorphic Encryption Algorithm for Secured Cloud Computing -- Relevance Feedback Base User Convenient Semantic Query Processing Using Neural Network -- Comparative Analysis of Decision Tree Algorithms -- Analysing the Genetic Diversity of Commonly Occurring Diseases -- Alternate Procedure for the Diagnosis of Malaria via Intuitionistic Fuzzy Sets -- A Deadline Aware Modified-Genetic Algorithm for Scheduling Jobs with Burst Time and Priorities -- Bio Inspired Computation for Optimizing Scheduling -- Segmentation of Mammograms using a Novel Intuitionistic Possibilstic Fuzzy C-Means Clustering Algorithm -- Wireless Monitoring and Indoor Navigation of a Mobile Robot using RFID -- A Note on q-Bernoulli-Euler Polynomials -- An Approach for Iris Segmentation in Constrained -- Environments -- Detection of Chronic Kidney Disease: A NN-GA Based Approach -- An Optimal Tree Based Routing Protocol Using Particle Swarm Optimization -- Sybil Attack Prevention Algorithm for Body Area Networks -- Surface Acoustic Wave E-nose Sensor Based Pattern Generation and Recognitionof Toxic Gases using Artificial Neural Network Techniques -- Pico-nym Cloud (PNC) a Method to Devise and Peruse Semantically Related Biological Patterns -- Assessment on VM Placement and VM Selection Strategies -- Distributed Denial of Service Attack Detection Using Ant Bee Colony and Artificial Neural Network in Cloud Computing -- Performance Evaluation of Neural Network Training Algorithms in Redirection Spam Detection -- Novel Method for Predicting Academic Performance of Students by Using Modified Particle Swarm Optimization (PSO) -- Medical Diagnosing of Canine Diseases Using Genetic Programming & Neural Networks -- A Comparative Study on Decision Making Capability Between Human and Artificial Intelligence.
Keywords: Artificial intelligence; Natural language processing (Computer science).; Computer simulation; Artificial Intelligence; Natural Language Processing (NLP).; Computer Modelling